Effect of fertilization with zinc in an agronomic fortification strategy in two potato varieties (Solanum tuberosum) in soils from the coast and highlands - Delgado, Luciana (Instituto Nacional de Innovación Agraria, 2018)
In this paper, scientific evidence to support the development of a larger scale project for fortified potato, as an alternative and sustainable solution in the medium and long term to combat the incidence of chronic malnutrition (hidden hunger) in the rural Andean population, is developed.